CRYSTAL STRUCTURES OF NATURAL ZEOLITES - Armbruster T.; Gunter M.E. (My University, 2001)
According to the recommended nomenclature for zeolite minerals (Coombs et al. 1998), there are more than eighty distinct zeolite species. Table 11 (see Appendix below) is a listing of the zeolite minerals discussed in this chapter. Although zeolites are not as geologically abundant or widespread as many other silicate mineral groups, there is perhaps more interest in the crystal structures of zeolites than in any other mineral group, as evidenced by the number of reported crystal structure refinements. Oxygen and silicon are the two most abundant elements in the Earth’s crust, followed by...